2016
DOI: 10.3233/jad-160593
|View full text |Cite
|
Sign up to set email alerts
|

BDNF Responses in Healthy Older Persons to 35 Minutes of Physical Exercise, Cognitive Training, and Mindfulness: Associations with Working Memory Function

Abstract: Brain-derived neurotrophic factor (BDNF) has a central role in brain plasticity by mediating changes in cortical thickness and synaptic density in response to physical activity and environmental enrichment. Previous studies suggest that physical exercise can augment BDNF levels, both in serum and the brain, but no other study has examined how different types of activities compare with physical exercise in their ability to affect BDNF levels. By using a balanced cross over experimental design, we exposed ninete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
126
2
7

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 155 publications
(146 citation statements)
references
References 80 publications
11
126
2
7
Order By: Relevance
“…This is consistent with previous studies in which physical exercise was demonstrated to be beneficial to motor and cognitive functions after stroke . We propose that EE in stroke survivors is implemented by 35‐min sessions of moderate physical exercise, cognitive training and mindfulness practice . This will have beneficial effects on reducing recurrent events and working memory function.…”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with previous studies in which physical exercise was demonstrated to be beneficial to motor and cognitive functions after stroke . We propose that EE in stroke survivors is implemented by 35‐min sessions of moderate physical exercise, cognitive training and mindfulness practice . This will have beneficial effects on reducing recurrent events and working memory function.…”
Section: Discussionsupporting
confidence: 90%
“…Similarly, a recent study with cyclists detected acute BDNF release during exercise and showed that intensified training improved the athletes' mood state, however, without modifying their plasma BDNF levels (Piacentini et al, ). The time latency for serum BDNF changes in response to behavioral and cognitive interventions is not clear‐cut and probably varies according to the health condition of the individual and the type of therapy (Hakansson et al, ; Kobayashi et al, ; Sanada et al, ; Turakitwanakan, Mekseepralard, & Busarakumtragul, ; Yamada, Yoshimura, Nakajima, & Nagata, ).…”
Section: Discussionmentioning
confidence: 99%
“…Critically, we did not observe a decline in MMSE scores across treatments in patients receiving either unilateral or bilateral treatment in the present study. In fact, given that c‐ECT led to elevations in BDNF in our sample and that BDNF is critically involved in cognitive processes , cognitive performance, assessed via the MMSE, may have been bolstered by monthly, ECT‐induced BDNF boosts. However, the MMSE is likely not sensitive enough to reveal these changes.…”
Section: Discussionmentioning
confidence: 88%